Molecular Simulations have Boosted Knowledge of CRISPR/Cas9: A Review - Ray, Angana; Felice, Rosa Di (Journal of Self Assembly and Molecular Electronics, 2023)
Genome editing allows scientists to change an organism’s DNA. One promis- ing genome editing protocol, already validated in living organisms, is based on clustered regularly interspaced short palindromic repeats (CRISPR)/Cas protein-nucleic acid complexes. When the CRISPR/Cas approach was first demonstrated in 2012, its advantages with respect to previously available techniques, such as zinc-finger nucleases (ZFNs) and transcription activator- like effector nucleases (TALENs), immediately got attention and the method has seen a surge of experimental and computational investigations since then. However, the molecular mechanisms involved in target DNA recognition and cleavage are still not completely resolved and need further attention. The large size and complex nature of CRISPR/Cas9 complexes has been a challenge for computational studies, but some seed results exist and are illuminating on the cleavage activity. In this short review, we present recent progress in studying CRISPR/Cas9 systems by molecular dynamics simulations with coarse-grained and atomistic descriptions, including enhanced sampling.